(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Sedimentation refers to a systematic process of particle transport to, placement on, withdrawal from, and maintenance on the seabed. Sediment is a naturally occurring component of aquatic habitats. However, the quantity and features of sediment have an impact the marine ecosystems' physical, chemical, and biological integrity. Deep sediments are the nation's most significant geological deposits. They serve as a record of our planet's reaction to circumstances at the sea surface, from which the majority of the material comes. They are also crucial aspects of energy flow through food webs and contribute to the operating of marine ecosystems. In addition, they are essential in sedimentary procedures such as carbon cycling and, nutrient and, waste malfunction, and abolishment. By studying the living and non-living variables contributing to the coastal system, the study ofstudying these sediments can be a tremendous asset for studying climate change and anthropogenic consequences (pollution associated with chemicals or metals)), and it can be a biological indicator of climatic changes anthropogenic consequences. So, the purpose of this review is to focus on the study of these sediments that are attributed to the impacts of urbanization along the marine coast by evaluating the Physicochemical characteristics of marine sediments that affect the marine bio-communities negatively or positively, and thus assessing the climatic changes and anthropogenic consequences that are associated with human health, industrial, and economic fields.